KNOWLEDGE ASSESSMENT OF NURSING STAFF REGARDING THE MANAGEMENT OF PERIPHERAL VENOUS CATHETERS IN TERTERYCARE HOSPITAL BOLAN MEDICAL COMPLEX QUETTA (The Research of Medical Science Review, 2024)
Background: Placement of Peripheral Venous Catheter (PVC) is one of the most commonly used procedures in any hospitals. Although incidence of infections associated with PVC are low however it is important that all the nursing staff are well aware of the guidelines regarding the care and management of PVC just to provide the better care to all the patients. The main aim of this audit was to assess the knowledge in each domain and bring in the improvements by the implementation of guidelines. Material and Method: It was a questionnaire based prospective cross sectional study that included 15 questions it was formed using the International guidelines mainly NICE guidelines. The 5 pillars of this study were VIP scoring, dressing technique, Safety measures, complications of PVC and appropriate documentation regarding PVC.. A total of 30 nursing staff from ICU and CCU of BMC ICQ were included in this audit over a period of 1 month (JULY 2024). Results: Among the 30 nurses, 85.5% already knew the proper dressing technique.86% knew about the complications. In addition, 65.5% were aware of the VIP scoring, 72% of staff documented the disposal of PVC, but only 46.2% were aware of the safety measures. Conclusion: 80% was chosen as the standard for determining proficiency in each section. Scores that were lower than 80% were regarded as inadequate, whilst scores that were higher than 80% were regarded as satisfactory. Based on this Audit it was evident that most of the staff lack knowledge regarding VIP scoring, safety measures and in the domain if proper documentation.